A method for protecting herd horses from blood-sucking insects that ensures organic food production - A. D. Reshetnikov; A. I. Barashkova (Российский паразитологический журнал, 2023)
The purpose of the research is to develop a method for protecting herd horses from dangerous blood-sucking dipterans that ensures organic meat production without pesticides.Materials and methods. Dangerous dipterans were collected and counted using an entomological net. The Diptera species identification was determined using the morphological keys. A new technology for protecting herd horses from harmful insects without pesticides used was implemented at Horobut LLC in the Megino-Kangalassky District, the Republic of Sakha (Yakutia) in 2021–2023. Pursuant to the Assignment and Regulations, a patent search was performed in the Russian scientific and technical literature on the subject “Develop methods for creating technologies to control and prevent animal diseases that ensure organic food production from conventional agricultural sectors in the Far North”.Results and discussion. The number of mosquitoes and horseflies that attack herd horses in Central Yakutia was established. In the morning and evening peaks, the number of mosquitoes for a 5-minute count was 397–456 mosquitoes belonging to 15 species of three genera: Aedes (Ochlerotatus), Culiseta and Anopheles. During a 15-minute count, the bait horse was attacked by 83 to 107 specimens of horseflies of 21 species and one subspecies of two genera, Hybomitra and Chrysops. For the first time in Central Yakutia, a method of protecting herd horses from attacks by blood-sucking insects was used with positive results without spraying animals with insecticides.